Treatment of palm oil mill effluent (POME) using membrane bioreactor - Abdul Aziz, Mohd Azoddein; Hazlan, Haris; Faten Ahada, Mohd Azli (The Malaysian Analytical Sciences Society, 2015)
Malaysia is the largest producer and exporter of palm oil. Palm oil mill effluent (POME) which is highly polluting effluent is becoming a major problem to environment as if it not being treated well before discharged based on standard limit imposed by The Malaysian Department of Environment (DOE) for effluent discharged. Samples from mixing ponds which act as activated sludge are collected and being analyze using water analyzer method to obtain parameters such as BOD, COD, suspended solid, turbidity and pH. Wastewater samples from facultative ponds are also being analyzed than mix with activated sludge treated in the bioreactor. Results from lab-scale bioreactor are used in membrane bioreactor pilot plant system to treat the wastewater. Results from bioreactor treatment in pilot plant scale show a decrement 61.2 % of BOD and 58.9% of COD, suspended solid and turbidity are also reducing up with pH in range of 5-9.After the wastewater was treated in the ultrafiltration membrane system, high quality water with total of deterioration for all parameter are up to 99.9% and pH up to7.39. This results show that the membrane bioreactor (MBR) treatment system are highly effective in treating POME.